Fiscal Policy and Income Determination - Samuelson, Paul A. (Quarterly Journal of Economics, 1942)
Scope of the paper, 575. — Negative multipliers, 576. — Level and growth of income in relation to level and growth of investment, 577. — Reaction of expenditure on revenue, 581. — Financial implications of deficits, 587.— Tertiary effects upon private investment, 595. — Public works vs. other expenditures, 599. — The multiplier and velocity approaches, 601. — Conclusion, 605.